The impact of domestic and global trade liberalization on five Southern African countries - Wobst, Peter (Informa UK Limited, 2003)
We compare the impact of alternative domestic and global trade liberalisation scenarios on five economies in Southern Africa. The study applies a computable general equilibrium model that employs standardised 12-sector social accounting matrices for Malawi, Mozambique, Tanzania, Zambia and Zimbabwe. The approach incorporates stylised features, such as own-household consumption and marketing margins, that are of particular importance when a majority of agricultural producers are not sufficiently integrated into formal markets and thus rely on own production to meet their daily diets. Hence, improved infrastructure implies lower marketing costs and better market integration, which translates to increased production opportunities. The comparison of the results across all five countries reveals that common policy measures have different impacts depending on the underlying economic structures." -- Author's Abstract